Hasbi Ash-Shiddieqy wa Tajdīd al-Fiqh fī Indūnīsīyā - M. Andi Sarjan (Studia Islamika, 1996)
Hasbi Ash-Shiddieqy (1904-1975) was a jurist reformer. The assertion may be begging the question: how can a renewal of thought suggests Jurist. Jurisprudence Is not it synonymous with stagnation? The reaction was understandable given the jurisprudence has long been described as Islamic thought static, dogmatic, rigid, and lacking an appreciation of social change. In this paper will be assessed on the role and influence of Hasbi Ash-Shiddieqy particularly among students of Islamic studies because most of his work in the form of text books which became a popular reference them as areas of fiqh, hadith, and 'ulum al-Qur'anDOI: 10.15408/sdi.v3i3.802